An Unusual FDG-PET/CT Documentation in Aleukemic Leukemia Cutis: Atypical Penile, Scrotal, and Leg Muscles Involvement - Sonavane, Sunita Nitin; Basu, Sandip (World Journal of Nuclear Medicine, 2022)
Aleukemic leukemia cutis (ALC) is a rare condition with a relatively poor prognosis, clinically presenting as skin and subcutaneous nodules commonly involving head and neck region with discrete atypical leukemic cells infiltrating in the skin on histopathology. The lesions on the genital area skin are seldom reported. A 49-year-old male presented with joint pains and multiple subcutaneous nodules clinically with biopsy proving it as leukemia cutis. Bone marrow aspiration and biopsy were suggestive of normocellular myeloid preponderant bone marrow with mild increase in eosinophils. The 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) revealed metabolically active FDG avid ill-defined soft tissue attenuation involving the entire length of penile shaft with central necrotic area, diffuse scrota skin thickening, and lateral compartment muscles of left leg, in addition to multiple hypermetabolic metastatic lymph nodes, and diffuse hypermetabolic marrow in humerii and femora. Despite prompt investigations and initiation of management, the patient succumbed in 15 days post-FDG PET/CT. The present report depicts an atypical case of ALC, with FDG PET-CT showing extensive and unusual sites of disease involvement, emphasizing its potential role in ALC.
Keywords: aleukemic leukemia cutis; 18F-FDG PET/CT; penile and scrotal involvement; cutaneous manifestation; cancer imaging